Unmaking the commons: Collective action, property rights and resource appropriation among (agro-) pastoralists in eastern Ethiopia - Beyene, Fekadu; Korf, Benedikt (International Food Policy Research Institute, 2008)
In Ethiopian development policies, pastoralist areas have recently attracted more attention. However, much debate and policy advice is still based on assumptions that see a sedentary lifestyle as the desirable development outcome for pastoralist communities. This paper investigates current practices of collective action and how these are affected by changing property rights in the pastoralist and agro-pastoralist economies of three selected sites in eastern Ethiopia. We describe forms of collective action in water and pasture resource management and analyze how changing property rights regimes affect incentives for collective action. We illustrate the distributional effects these practices are having on (agro-) pastoralist communities and how these practices are being influenced by the broader political and economic dynamisms of the area.